Perovskite ink, perovskite light absorption layer and preparation method thereof, and perovskite solar cell

By using low boiling point, high saturation vapor pressure organic solvent containing single bonds of carbon and oxygen, the uniformity problem of large-area narrow band gap lead-tin blended perovskite film is solved, and the photoelectric conversion efficiency of perovskite solar cells is improved and productivity.

CN119119796APending Publication Date: 2024-12-13RENSHUO SOLAR ENERGY (SUZHOU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411277886.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art is difficult to achieve uniform preparation of large-area narrow bandgap lead-tin blended perovskite films, which limits the industrialization process of all-perovskite stacked batteries.

Method used

Using a low boiling point, high saturation vapor pressure organic solvent containing carbon and oxygen single bonds, the uniform coating of perovskite ink and the efficient preparation of thin films is achieved through rapid evaporation and uniform crystallization.

Benefits of technology

It improves the photoelectric conversion efficiency of large-area perovskite solar cell modules, reduces material costs and production costs, and achieves uniformity and efficient mass production of perovskite films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119796A_ABST
    Figure CN119119796A_ABST
Patent Text Reader

Abstract

The invention provides perovskite ink, a perovskite light absorption layer, a preparation method of the perovskite light absorption layer and a perovskite solar cell. The perovskite ink comprises a perovskite material and an organic solvent containing a carbon-oxygen single bond, and the organic solvent containing the carbon-oxygen single bond comprises at least one of a methoxy organic solvent, an alcohol organic solvent or an epoxy organic solvent. The perovskite ink provided by the invention can evaporate quickly and can realize uniform nucleation and uniform crystallization, so that the uniformity of large-area preparation of a narrow-band-gap lead-tin blended perovskite thin film is improved, and the photoelectric conversion efficiency of a large-area perovskite solar cell module is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solar cell materials, and in particular relates to a perovskite ink, a perovskite light absorbing layer and a preparation method thereof, and a perovskite solar cell. Background Art

[0002] In recent years, the technology of all-perovskite tandem solar cells has developed rapidly, and the cell efficiency has exceeded 30%. Because it is composed of two cells with different bandgap absorbers, it can absorb sunlight with a wider range of wavelengths through differential absorption, reduce light and heat loss, and thus improve the cell conversion efficiency. At present, the all-perovskite tandem cell is composed of a 1.77eV wide-bandgap perovskite sub-cell at the top and a 1.22eV narrow-bandgap perovskite sub-cell at the bottom. Its advantage is that the band gaps of both sub-cells can be flexibly adjusted, which can maximize the efficient use of the solar spectrum while taking into account the characteristics of low production costs. In order to further promote the industrial application of all-perovskite tandem cells, large-scale mass production preparation technology has attracted much attention. However, the photoelectric conversion efficiency of large-area all-perovskite tandem cell components is now far behind that of small-area tandem cells, which restricts the industrialization process of perovskite tandem cells. This is mainly limited by the difficulty in uniform preparation of large-area narrow-bandgap lead-tin blended perovskite films.

[0003] Based on this, the development of uniform preparation technology for large-area narrow-bandgap lead-tin blended perovskite films is of great significance for realizing mass-producible high-efficiency all-perovskite stacked battery components. At present, the preparation methods of narrow-bandgap lead-tin blended perovskite films disclosed in the prior art are mostly anti-solvent-assisted methods based on solution coating. Among them, the solvent components mainly include a mixed solvent of N, N-dimethylformamide and dimethyl sulfoxide, or ionic salts disclosed in Chinese patents CN115425150A and CN114709337A, thereby preparing a narrow-bandgap lead-tin blended perovskite film. However, the mixed solvent of N, N-dimethylformamide and dimethyl sulfoxide has the disadvantages of a high boiling point and a low saturated vapor pressure, so it is not suitable for the preparation of large-area narrow-bandgap lead-tin blended perovskite films, and ionic salts also need to use auxiliary solvents such as N, N-dimethylformamide, and cannot achieve uniform preparation of large-scale narrow-bandgap lead-tin blended perovskite films.

[0004] Therefore, in this field, there is an urgent need to develop a uniform preparation technology for large-area narrow-bandgap lead-tin blended perovskite films to solve the above problems. Summary of the invention

[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a perovskite ink, a perovskite light absorbing layer and a preparation method thereof, and a perovskite solar cell. The present invention provides a perovskite ink that evaporates quickly and can achieve uniform nucleation and uniform crystallization, thereby improving the uniformity of preparing a narrow-bandgap lead-tin blended perovskite film over a large area, and improving the photoelectric conversion efficiency of a large-area perovskite solar cell module.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a perovskite ink, comprising a perovskite material and an organic solvent containing carbon-oxygen single bonds, wherein the organic solvent containing carbon-oxygen single bonds comprises at least one of a methoxy organic solvent, an alcohol organic solvent or an epoxy organic solvent.

[0008] The present invention adopts an organic solvent containing a carbon-oxygen single bond with a low boiling point and a high saturated vapor pressure, so that the organic solvent in the wet film of the perovskite ink can evaporate quickly and the perovskite material can nucleate rapidly after coating, thereby achieving the effect of uniform crystallization. Compared with traditional organic solvents, the organic solvent containing a carbon-oxygen single bond provided by the present invention has a fast volatilization rate, which can achieve the technical effects of rapid coating and rapid crystallization, thereby greatly shortening the time cost of preparing the perovskite light-absorbing layer, and improving the production efficiency of mass production. In addition, due to the fast evaporation rate of the organic solvent containing a carbon-oxygen single bond, when preparing a perovskite film with the same thickness, the required concentration of the perovskite ink is lower, thereby reducing the material cost and the production cost.

[0009] Preferably, the organic solvent containing a carbon-oxygen single bond comprises a combination of at least two of a methoxy organic solvent, an alcohol organic solvent or an epoxy organic solvent, preferably a combination of a methoxy organic solvent and an epoxy organic solvent. The present invention adopts a combination solvent of a methoxy organic solvent and an epoxy organic solvent to further achieve the technical effect of improving the crystallization quality of the perovskite film and the crystallization uniformity of a large-area narrow-bandgap perovskite film.

[0010] Furthermore, the volume percentage of the methoxy organic solvent in the combination of the methoxy organic solvent and the epoxy organic solvent is 1%-99%, preferably 50%-99%, for example, 1%, 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 99%, etc. The present invention controls the volume content of the methoxy organic solvent within a suitable numerical range by regulating the volume content relationship between the combination of the methoxy organic solvent and the epoxy organic solvent, thereby ensuring that the perovskite material can be completely dissolved.

[0011] Preferably, the methoxy organic solvent includes any one or a combination of at least two of 3-methoxy-1-propanol, methoxymethanol, 2-methoxyethanol, 4-methoxyphenol, methoxyacetone, 1-bromo-2-(methoxymethoxy)ethane, methoxyacetic acid or methoxyacetonitrile, preferably 2-methoxyethanol.

[0012] Furthermore, the volume percentage of 2-methoxyethanol in the organic solvent containing carbon-oxygen single bonds is 50%-100%, for example, 50%, 60%, 70%, 80%, 90%, 100%, etc.

[0013] Preferably, the alcohol organic solvent includes any one of ethanol, n-propanol, isopropanol, n-butanol, n-hexanol or n-pentanol, or a combination of at least two thereof, preferably ethanol.

[0014] Furthermore, the volume percentage of ethanol in the organic solvent containing carbon-oxygen single bonds is 0%-50%, for example, 0%, 2%, 5%, 10%, 20%, 30%, 40%, 50%, etc. If the volume percentage of ethanol is high, it will affect the solubility of the perovskite material and cause it to precipitate.

[0015] Preferably, the epoxy organic solvent includes any one or a combination of at least two of tetrahydrofuran, 1,3-dioxolane, 1,2-butylene oxide, oxetane, 3-ethyl-3-oxetanemethanol, tetrahydropyran or 1,4-thioxane, preferably tetrahydrofuran.

[0016] Furthermore, the volume percentage of tetrahydrofuran in the organic solvent containing carbon-oxygen single bonds is 0%-50%, for example, 0%, 2%, 5%, 10%, 20%, 30%, 40%, 50%, etc. If the volume percentage of tetrahydrofuran is high, it will affect the solubility of the perovskite material and cause its precipitation.

[0017] Preferably, the perovskite material is of ABX3 type structure, wherein the A-site ions include at least one of cesium ions, methylamine groups or guanidine groups, the B-site ions include divalent metal cations, and the X-site ions include halogen anions.

[0018] Preferably, the divalent metal cations include lead ions (Pb 2+ ) and tin ions (Sn 2+ ), wherein the molar percentage of the tin ions is 10%-90%, for example, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, etc.

[0019] In the present invention, the X-site ions include halogen anions, such as iodide ions (I - ), bromide ion (Br- ) and chloride ions (Cl - ) or a combination of at least two of them in any proportion.

[0020] Preferably, the concentration of the perovskite material in the perovskite ink is 0.1mol / L-2.0mol / L, for example, it can be 0.1mol / L, 0.2mol / L, 0.5mol / L, 0.8mol / L, 1.0mol / L, 1.2mol / L, 1.5mol / L, 1.8mol / L, 2.0mol / L, etc.

[0021] In a second aspect, the present invention provides a method for preparing a perovskite light absorbing layer, the method comprising the following steps:

[0022] The perovskite ink according to the first aspect is coated on the surface of a substrate, and the perovskite light-absorbing layer is obtained after annealing.

[0023] In the present invention, the coating method exemplarily includes at least one of a doctor blade coating method, a slit coating method or a spray coating method, wherein the perovskite ink is coated on a flexible or rigid substrate, and a perovskite light absorbing layer is formed after annealing.

[0024] In the present invention, the perovskite light absorbing layer is prepared by the blade coating or slit coating method, and the coating speed can be 1-1000 mm / s, for example, 1 mm / s, 5 mm / s, 10 mm / s, 50 mm / s, 100 mm / s, 200 mm / s, 300 mm / s, 400 mm / s, 500 mm / s, 600 mm / s, 700 mm / s, 800 mm / s, 900 mm / s, 1000 mm / s, etc. Further, the coating speed is preferably 30 mm / s.

[0025] In the present invention, the auxiliary crystallization method in the preparation process of the perovskite light absorbing layer can exemplarily adopt at least one of the hot plate heating method, air blowing method, vacuum flash evaporation method or anti-solvent method, but is not limited to the above auxiliary crystallization methods.

[0026] In the present invention, the annealing step includes transferring the substrate to an environment of 50-150°C (for example, 50°C, 80°C, 100°C, 120°C, 150°C, etc.) for heat treatment for 3-30 minutes (for example, 3 minutes, 5 minutes, 8 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, etc.) to remove the residual solvent, and finally form a dense and uniform perovskite light-absorbing layer. If the annealing temperature is high and the time is long, it will have an adverse effect on the photoelectric performance of the perovskite solar cell; if the annealing temperature is low and the time is short, the residual solvent will not be fully removed. Further, the annealing temperature is preferably 90°C and the time is 10 minutes.

[0027] In a third aspect, the present invention provides a perovskite light absorbing layer, wherein the perovskite light absorbing layer is prepared by the method for preparing a perovskite light absorbing layer described in the second aspect.

[0028] Preferably, the perovskite light absorbing layer is a lead-tin blended perovskite light absorbing layer.

[0029] In the present invention, the thickness of the perovskite light absorbing layer is 300-2000nm, preferably 600-1000nm, for example, it can be 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1200nm, 1500nm, 1800nm, 2000nm, etc.

[0030] In a fourth aspect, the present invention provides a perovskite solar cell, wherein the perovskite solar cell comprises the perovskite light absorbing layer according to the third aspect.

[0031] In the present invention, the perovskite light-absorbing layer according to the third aspect is applied to a perovskite solar cell to obtain a regular structure perovskite solar cell or a reverse structure perovskite solar cell.

[0032] In the present invention, the perovskite light absorbing layer according to the third aspect can be applied to different areas (0.03-7200cm 2 , for example, it can be 0.03 cm 2 , 0.1cm 2 , 1cm 2 , 5cm 2 、10cm 2 , 50cm 2 , 100cm 2 , 200cm 2 , 500cm 2 , 1000cm 2 , 2000cm 2 、3000cm2 、4000cm 2 、5000cm 2 、6000cm 2 、7000cm 2 、7200cm 2 The invention relates to single-junction or tandem perovskite solar cells and their components, and is further preferably a full perovskite tandem solar cell.

[0033] In the present invention, the perovskite solar cell further includes a transparent conductive substrate, a hole transport layer, an electron transport layer and a back electrode.

[0034] In the present invention, the transparent conductive substrate exemplarily includes at least one of an indium tin oxide (ITO) substrate, an indium tungsten oxide (IWO) substrate, a fluorine-doped tin oxide (FTO) substrate, an indium zinc oxide (IZO) substrate or an aluminum-doped zinc oxide (AZO) substrate.

[0035] In the present invention, the material of the hole transport layer exemplarily includes at least one of PVK, MeO-2PACz, 2PACz, Me-4PACz, CuI, spiro-TTB, NiO, MoO3, Cu2O, CuI, CuPc, CuSCN, redox graphene, PTAA, PEDOT:PSS or Ploy-TPD. The thickness of the hole transport layer is 40-50nm, for example, 40nm, 42nm, 45nm, 48nm, 50nm, etc.

[0036] In the present invention, the material of the electron transport layer exemplarily includes C 60 , C 70 , graphene, PCBM, ICBA, Nb2O5, TiO2, SnO2 or ZnO.

[0037] In the present invention, the material of the back electrode exemplarily includes at least one of gold, silver, copper, titanium, chromium, nickel or aluminum.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] The present invention provides a perovskite ink, which can achieve the effect of uniform crystallization by using an organic solvent containing a carbon-oxygen single bond with a low boiling point and a high saturated vapor pressure, so that the organic solvent in the wet film of the perovskite ink can evaporate quickly and the perovskite material can nucleate quickly after coating. Compared with traditional organic solvents, the organic solvent containing a carbon-oxygen single bond provided by the present invention has a fast volatilization rate, which can achieve the technical effects of rapid coating and rapid crystallization, thereby greatly shortening the time cost of preparing the perovskite light-absorbing layer, and improving the production efficiency of mass production. In addition, due to the fast evaporation rate of the organic solvent containing a carbon-oxygen single bond, when preparing a perovskite film with the same thickness, the required concentration of the perovskite ink is lower, thereby reducing the material cost and the production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a comparison chart of the uniformity of the lead-tin blended perovskite films prepared using different solvents in Examples 1-2 and Comparative Example 1.

[0041] Figure 2 This is a structural diagram of the perovskite / perovskite double-section stacked component in Application Example 1.

[0042] Figure 3 This is a physical picture of the perovskite / perovskite double-section stacked component in Application Example 1.

[0043] Figure 4 This is the current-voltage curve of the perovskite / perovskite double-layer stacked component in Application Example 2. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further described below by combining the accompanying drawings and specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0045] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0046] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0047] Example 1

[0048] This embodiment provides a perovskite ink for preparing a large-area narrow-bandgap lead-tin blended perovskite film, and examines its uniformity.

[0049] The method for preparing the narrow bandgap lead-tin blended perovskite film comprises the following steps:

[0050] (1) An ITO transparent conductive glass substrate having a size of 10 cm×10 cm was scrubbed with deionized water mixed with an ITO cleaning solution, and then ultrasonicated with deionized water, acetone, and isopropanol for 30 min each to obtain a cleaned ITO transparent conductive glass substrate.

[0051] (2) The cleaned ITO transparent conductive glass substrate was blown clean with a N2 air gun and pretreated with UV ozone for 18 minutes.

[0052] (3) A layer of poly (3,4-ethylenedioxythiophene): polystyrene sulfonate (PEDOT:PSS) with a thickness of 45 nm was prepared on the ITO transparent conductive glass substrate pretreated with UV ozone as a hole transport layer. The PEDOT:PSS solution was spin-coated on the ITO transparent conductive glass substrate and annealed on a hot plate at 150°C for 20 minutes. The substrate with the hole transport layer was stored in a glove box filled with nitrogen.

[0053] (4) Weigh MA according to the molar ratio in a glove box filled with nitrogen. 0.3 FA 0.7 Pb 0.5 Sn 0.5 The perovskite precursor material of I3 is added with 5% molar percentage of stannous fluoride (SnF2) (Pb 2+ Sn 2+ The weighed drugs were dissolved in 2-methoxyethanol, and 5% by volume of dimethyl sulfoxide (DMSO) was added as a complexing agent (based on the volume of 2-methoxyethanol as 100%), and stirred for 1 hour to prepare a narrow-bandgap lead-tin blended perovskite precursor solution with a concentration of 1.2 mol / L.

[0054] (5) In a glove box, a narrow bandgap lead-tin blended perovskite film was prepared by a blade coating method. The solvent was evaporated with an air knife. The blade coating speed was 30 mm / s, the air pressure of the air knife was 0.4 MPa, the film thickness was 1000 nm, and it was annealed on a hot plate at 90 °C for 7 min to obtain a crystallized perovskite light-absorbing layer.

[0055] (6) The uniformity of the deposited large-area narrow-bandgap lead-tin blended perovskite film was characterized by scanning electron microscopy testing.

[0056] pass Figure 1 It can be seen from the actual film image and scanning electron microscope image that the perovskite ink using 2-methoxyethanol as the solvent greatly improves the uniformity of the prepared narrow bandgap lead-tin blended perovskite film.

[0057] Application Example 1

[0058] In this application example, the perovskite light absorbing layer is prepared according to the deposition method described above. Figure 2 The area shown in the structure is 65cm 2 The specific preparation process of the perovskite-perovskite double-layer battery assembly is as follows:

[0059] (1) ITO transparent conductive glass substrate was prepared by laser scribing P1.

[0060] (2) The ITO transparent conductive glass substrate was scrubbed with deionized water, and then ultrasonicated with deionized water, acetone and isopropanol for 30 min each. The cleaned ITO transparent conductive glass substrate was blown clean with a N2 air gun and pretreated with ultraviolet ozone for 18 min.

[0061] (3) A hole transport layer is deposited on the ITO transparent conductive glass substrate after UV ozone pretreatment, and the material of the hole transport layer is nickel oxide.

[0062] (4) In a glove box filled with nitrogen, weigh Cs and 0.35 FA 0.65 PbI 1.8 Br 1.2 The perovskite precursor materials are: CsI, FAI, PbI2 and PbBr2, and the above components are dissolved in a mixed solvent (including DMF and DMSO) with a volume ratio of 4:1 to obtain a wide bandgap perovskite precursor solution with a concentration of 1.5 mol / L. The wide bandgap perovskite film is prepared by blade coating, and the thickness of the film is 400 nm.

[0063] (5) A 30 nm thick C layer was deposited by thermal evaporation. 60 .

[0064] (6) Tin dioxide (SnO2) with a thickness of 60 nm is deposited by atomic layer deposition (ALD).

[0065] (7) A conductive gold layer with a thickness of 0.5 nm was deposited by thermal evaporation.

[0066] (8) Depositing a hole transport layer, wherein the material of the hole transport layer is PEDOT:PSS.

[0067] (9) A narrow bandgap lead-tin blended perovskite film was prepared by a doctor blade coating method using 2-methoxyethanol as the solvent of the perovskite ink. The thickness of the film was 1000 nm.

[0068] (10) A 30 nm thick C 60 .

[0069] (11) SnO2 with a thickness of 10 nm was deposited by atomic layer deposition.

[0070] (12) P2 was prepared using laser scribing.

[0071] (13) SnO2 with a thickness of 5 nm was deposited by atomic layer deposition.

[0072] (14) A layer of Cu with a thickness of 200 nm was deposited by thermal evaporation as the back electrode.

[0073] (15) P3 was prepared using laser scribing.

[0074] The area prepared in this application example is 65cm 2 The actual picture of the perovskite-perovskite double-layer battery module is as follows Figure 3 shown.

[0075] Example 2

[0076] This embodiment provides a perovskite ink for preparing a large-area narrow-bandgap lead-tin blended perovskite film, and examines its uniformity.

[0077] The method for preparing the narrow bandgap lead-tin blended perovskite film comprises the following steps:

[0078] (1) An ITO transparent conductive glass substrate having a size of 10 cm×10 cm was scrubbed with deionized water mixed with an ITO cleaning solution, and then ultrasonicated with deionized water, acetone, and isopropanol for 30 min each to obtain a cleaned ITO transparent conductive glass substrate.

[0079] (2) The cleaned ITO transparent conductive glass substrate was blown clean with a N2 air gun and pretreated with UV ozone for 18 minutes.

[0080] (3) A layer of poly (3,4-ethylenedioxythiophene): polystyrene sulfonate (PEDOT:PSS) with a thickness of 45 nm was prepared on the ITO transparent conductive glass substrate pretreated with UV ozone as a hole transport layer. The PEDOT:PSS solution was spin-coated on the ITO transparent conductive glass substrate and annealed on a hot plate at 150°C for 20 minutes. The substrate with the hole transport layer was stored in a glove box filled with nitrogen.

[0081] (4) Weigh MA according to the molar ratio in a glove box filled with nitrogen. 0.3 FA 0.7 Pb 0.5 Sn 0.5 The perovskite precursor material of I3 is added with 5% molar percentage of stannous fluoride (SnF2) (Pb 2+ Sn 2+The weighed drugs were dissolved in a mixed solvent (including 2-methoxyethanol and tetrahydrofuran in a volume ratio of 1:1), and 5% by volume of dimethyl sulfoxide (DMSO) was added as a complexing agent (based on the volume of the mixed solvent as 100%), and stirred for 1 hour to prepare a narrow bandgap lead-tin blended perovskite precursor solution with a concentration of 1.2 mol / L.

[0082] (5) In a glove box, a narrow bandgap lead-tin blended perovskite film was prepared by a blade coating method. The solvent was evaporated with an air knife. The blade coating speed was 30 mm / s, the air pressure of the air knife was 0.4 MPa, the film thickness was 1000 nm, and it was annealed on a hot plate at 90 °C for 7 min to obtain a crystallized perovskite light-absorbing layer.

[0083] (6) The uniformity of the deposited large-area narrow-bandgap lead-tin blended perovskite film was characterized by scanning electron microscopy testing.

[0084] pass Figure 1 It can be seen from the actual film image and scanning electron microscope image that the use of perovskite ink including 2-methoxyethanol and tetrahydrofuran as a mixed solvent greatly improves the uniformity of the prepared narrow bandgap lead-tin blended perovskite film.

[0085] Application Example 2

[0086] In this application example, a 65 cm2 perovskite light absorbing layer was prepared according to the above-mentioned deposition method. 2 The specific preparation process of the perovskite-perovskite double-layer battery assembly is as follows:

[0087] (1) ITO transparent conductive glass substrate was prepared by laser scribing P1.

[0088] (2) The ITO transparent conductive glass substrate was scrubbed with deionized water, and then ultrasonicated with deionized water, acetone and isopropanol for 30 min each. The cleaned ITO transparent conductive glass substrate was blown clean with a N2 air gun and pretreated with ultraviolet ozone for 18 min.

[0089] (3) A hole transport layer is deposited on the ITO transparent conductive glass substrate after UV ozone pretreatment, and the material of the hole transport layer is nickel oxide.

[0090] (4) In a glove box filled with nitrogen, weigh Cs and 0.35 FA 0.65 PbI 1.8 Br 1.2The perovskite precursor materials are: CsI, FAI, PbI2, PbBr2, and the above components are dissolved in a mixed solvent (including DMF and DMSO) with a volume ratio of 4:1 to obtain a wide bandgap perovskite precursor solution with a concentration of 1.5 mol / L. The wide bandgap perovskite film is prepared by blade coating, and the thickness of the film is 400 nm.

[0091] (5) A 30 nm thick C layer was deposited by thermal evaporation. 60 .

[0092] (6) Tin dioxide (SnO2) with a thickness of 60 nm is deposited by atomic layer deposition (ALD).

[0093] (7) A conductive gold layer with a thickness of 0.5 nm was deposited by thermal evaporation.

[0094] (8) Depositing a hole transport layer, wherein the material of the hole transport layer is PEDOT:PSS.

[0095] (9) A narrow bandgap lead-tin blended perovskite film was prepared by a doctor blade coating method using a perovskite ink containing 2-methoxyethanol and tetrahydrofuran in a volume ratio of 1:1 as a mixed solvent. The thickness of the film was 1000 nm.

[0096] (10) A 30 nm thick C 60 .

[0097] (11) SnO2 with a thickness of 10 nm was deposited by atomic layer deposition.

[0098] (12) P2 was prepared using laser scribing.

[0099] (13) SnO2 with a thickness of 5 nm was deposited by atomic layer deposition.

[0100] (14) A layer of Cu with a thickness of 200 nm was deposited by thermal evaporation as the back electrode.

[0101] (15) P3 was prepared using laser scribing.

[0102] Example 3

[0103] The difference between this embodiment and embodiment 2 is that in step (4), the mixed solvent consisting of 2-methoxyethanol and tetrahydrofuran in a volume ratio of 1:1 is replaced by a mixed solvent of 2-methoxyethanol and 1,3-dioxolane in a volume ratio of 1:1 with equal contents, and the rest is the same as embodiment 2.

[0104] Application Example 3

[0105] The difference between this application example and application example 2 is that in step (9), the mixed solvent consisting of 2-methoxyethanol and tetrahydrofuran in a volume ratio of 1:1 is replaced by a mixed solvent of 2-methoxyethanol and 1,3-dioxolane in a volume ratio of 1:1 with equal contents, and the rest is the same as application example 2.

[0106] Example 4

[0107] The difference between this embodiment and embodiment 2 is that in step (4), the mixed solvent consisting of 2-methoxyethanol and tetrahydrofuran in a volume ratio of 1:1 is replaced with ethanol in an equal content, and the rest is the same as embodiment 2.

[0108] Application Example 4

[0109] The difference between this application example and application example 2 is that in step (9), the mixed solvent consisting of 2-methoxyethanol and tetrahydrofuran in a volume ratio of 1:1 is replaced with ethanol of the same content, and the rest is the same as application example 2.

[0110] Example 5

[0111] The difference between this embodiment and embodiment 2 is that in step (4), the mixed solvent consisting of 2-methoxyethanol and tetrahydrofuran in a volume ratio of 1:1 is replaced by a mixed solvent of 2-methoxyethanol, tetrahydrofuran and ethanol in a volume ratio of 2:1:1 with equal contents, and the rest is the same as embodiment 2.

[0112] Application Example 5

[0113] The difference between this application example and application example 2 is that in step (9), the mixed solvent consisting of 2-methoxyethanol and tetrahydrofuran in a volume ratio of 1:1 is replaced by a mixed solvent of 2-methoxyethanol, tetrahydrofuran and ethanol in a volume ratio of 2:1:1 with equal contents, and the rest is the same as application example 2.

[0114] Comparative Example 1

[0115] The difference between this comparative example and Example 2 is that in step (4), the mixed solvent consisting of 2-methoxyethanol and tetrahydrofuran in a volume ratio of 1:1 is replaced by an equal amount of N,N-dimethylformamide, and the rest is the same as Example 2.

[0116] Comparative application example 1

[0117] The difference between this comparative application example and application example 2 is that in step (9), the mixed solvent consisting of 2-methoxyethanol and tetrahydrofuran in a volume ratio of 1:1 is replaced by an equal amount of N,N-dimethylformamide, and the rest is the same as application example 2.

[0118] Comparative Example 2

[0119] The difference between this comparative example and Example 2 is that in step (4), the mixed solvent consisting of 2-methoxyethanol and tetrahydrofuran in a volume ratio of 1:1 is replaced by acetonitrile in an equal content, and the rest is the same as Example 2.

[0120] Comparative Application Example 2

[0121] The difference between this comparative application example and application example 2 is that in step (9), the mixed solvent consisting of 2-methoxyethanol and tetrahydrofuran in a volume ratio of 1:1 is replaced by acetonitrile of the same content, and the rest is the same as application example 2.

[0122] The perovskite-perovskite tandem solar cell modules in the above application examples and comparative application examples were tested using a solar cell testing system. The test results are shown in Table 1:

[0123] Table 1

[0124] Photoelectric conversion efficiency (%) Application Example 1 24.2 Application Example 2 24.6 Application Example 3 24.5 Application Example 4 24.5 Application Example 5 24.4 Comparative application example 1 23 Comparative Application Example 2 23.5

[0125] As can be seen from Table 1, the photoelectric conversion efficiency of the perovskite-perovskite laminated solar cell module prepared by the acetonitrile solvent (Comparative Application Example 2) used in the prior art is higher than the photoelectric conversion efficiency of the perovskite-perovskite laminated solar cell module prepared by using the N,N-dimethylformamide solvent (Comparative Application Example 1), indicating that the acetonitrile solvent provided in Comparative Application Example 2 can improve the uniformity and crystal quality of the perovskite material to a certain extent. However, the photoelectric conversion efficiency of the perovskite-perovskite laminated solar cell module prepared by the technical solution proposed in the present invention (Application Examples 1-5) is not less than 24%, which shows that the present invention uses an organic solvent containing a carbon-oxygen single bond with a low boiling point and a high saturated vapor pressure, so that the uniformity and crystal quality of the narrow bandgap lead-tin blended perovskite are significantly improved compared with the conventional solvents disclosed in the prior art.

[0126] from Figure 4 It can be seen that compared with the single solvent used in Application Example 1, the uniformity of the large-area narrow-bandgap lead-tin blended perovskite film finally prepared is improved due to the use of the specific type of combined solvent provided in Application Example 2 of the present invention as the perovskite ink, and then applied to the perovskite-perovskite tandem solar cell module to obtain a higher photoelectric conversion efficiency of 24.6%, and the open circuit voltage, short-circuit current density and fill factor of the perovskite-perovskite tandem solar cell module are all improved.

[0127] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A perovskite ink, characterized in that: The perovskite ink comprises a perovskite material and an organic solvent containing a carbon-oxygen single bond, wherein the organic solvent containing a carbon-oxygen single bond comprises at least one of a methoxy organic solvent, an alcohol organic solvent or an epoxy organic solvent.

2. The perovskite ink according to claim 1, characterized in that The organic solvent containing a carbon-oxygen single bond comprises a combination of at least two of a methoxy organic solvent, an alcohol organic solvent or an epoxy organic solvent, preferably a combination of a methoxy organic solvent and an epoxy organic solvent; The volume percentage of the methoxy organic solvent in the combination of the methoxy organic solvent and the epoxy organic solvent is 1%-99%, preferably 50%-99%.

3. The perovskite ink according to claim 1, characterized in that The methoxy organic solvent includes any one or a combination of at least two of 3-methoxy-1-propanol, methoxymethanol, 2-methoxyethanol, 4-methoxyphenol, methoxyacetone, 1-bromo-2-(methoxymethoxy)ethane, methoxyacetic acid or methoxyacetonitrile, preferably 2-methoxyethanol; The volume percentage of 2-methoxyethanol in the organic solvent containing carbon-oxygen single bonds is 50%-100%.

4. The perovskite ink according to claim 1, characterized in that The alcohol organic solvent includes any one of ethanol, n-propanol, isopropanol, n-butanol, n-hexanol or n-pentanol, or a combination of at least two thereof, preferably ethanol; The volume percentage of ethanol in the organic solvent containing carbon-oxygen single bonds is 0%-50%.

5. The perovskite ink according to claim 1, characterized in that The epoxy organic solvent includes any one or a combination of at least two of tetrahydrofuran, 1,3-dioxolane, 1,2-butylene oxide, oxetane, 3-ethyl-3-oxetanemethanol, tetrahydropyran or 1,4-thioxane, preferably tetrahydrofuran; The volume percentage of tetrahydrofuran in the organic solvent containing carbon-oxygen single bonds is 0%-50%.

6. The perovskite ink according to claim 1, characterized in that The perovskite material has an ABX3 type structure, wherein the A-site ions include at least one of cesium ions, methylamine groups or methylammonium groups, the B-site ions include divalent metal cations, and the X-site ions include halogen anions; The divalent metal cations include a combination of lead ions and tin ions, wherein the molar percentage of the tin ions is 10%-90%; The concentration of the perovskite material in the perovskite ink is 0.1 mol / L-2.0 mol / L.

7. A method for preparing a perovskite light absorbing layer, characterized in that: The method comprises the following steps: The perovskite ink according to any one of claims 1 to 6 is coated on the surface of a substrate, and the perovskite light absorbing layer is obtained after annealing.

8. A perovskite light absorbing layer, characterized in that: The perovskite light absorbing layer is prepared by the method for preparing a perovskite light absorbing layer according to claim 7.

9. The perovskite light absorbing layer according to claim 8, characterized in that: The perovskite light absorbing layer is a lead-tin mixed perovskite light absorbing layer.

10. A perovskite solar cell, characterized in that: The perovskite solar cell comprises the perovskite light-absorbing layer according to claim 8 or 9.